Reactivity in micelles - are we really able to design micellar catalysts? - Jurok, Radek; Svobodová, Eva; Cibulka, Radek; Hampl, František (Collection of Czechoslovak Chemical Communications, 2008)
Coordination of lipophilic alkyl pyridin-2-yl ketoximes 1 to Ni2+ ions, reduction of lipophilic 3-alkoxyacetophenones 2 with sodium borohydride, and alkaline hydrolysis of 4-nitrophenyl diphenyl phosphate (PNPDPP) were employed as probes in the investigation which factors may influence the reactivity of organic compounds in micellar systems. In all these reactions, a lipophilic substrate solubilized in micellar core was attacked by a hydrophilic reagent from the bulk aqueous phase. To evaluate the contribution of electrostatic interactions between the micellar surface charge and the reagent to the observed reactivity, we combined reactions involving the reagents with opposite polarity (Ni2+ cations and borohydride or hydroxide anions) with positively charged micelles of hexadecyltrimethylammonium chloride (CTAC) or bromide (CTAB) and negatively charged micelles of sodium dodecyl sulfate (SDS). Non-ionic micelles (Triton X-100 or Brij 35) served as a reference. The results of the kinetic studies give evidence that each of the investigated systems has unique properties going in particular aspects beyond the scope of the generally accepted concepts of reactivity in micelles.
Keywords: Micelles; financování organizované; vztahy mezi strukturou a aktivitou; Financing, Organized; Catalysis; Emulsions; Structure-Activity Relationship; emulze; katalýza; micely